Moment stability analysis method for determining safety factors for articulated concrete blocks - Cox, Amanda L., author; Thornton, Christopher I., advisor; Vlachos, Evan, committee member; Abt, Steven R., committee member; Watson, Chester C., committee member (Colorado State University. Libraries, 2010)
Articulated concrete block (ACB) revetment systems are widely used for channel lining and embankment protection. Available information pertaining to testing and analysis of ACB systems was identified. Current approaches for prediction of ACB system stability are based on a moment stability analysis and utilize shear stress to account for all hydrodynamic forces. Assumptions utilized in the moment stability analysis derivations were identified and the applicability to channelized and steep-slope conditions was investigated. The assumption of equal lift and drag forces was determined to be non-conservative and the most influential to computed safety factors. A database of twenty-four tests encompassing both channelized and overtopping conditions was compiled from available data for three ACB systems. Safety factors were computed using the current state-of-the-practice design methodology for each test. The current design methodology proved accurate at predicting the point of instability for five out of the nine total tested ACB installations. A new safety factor design methodology was developed using a moment stability analysis coupled with the computation of hydrodynamic forces using both boundary shear stress and flow velocity. Lift coefficients were calibrated for each of the three ACB systems within the database. Safety factors were computed using the new safety factor method and the calibrated lift coefficients. The new safety factor design method proved accurate at predicting stability for eight of the nine total tested ACB installations.
Department Head: Luis A. Garcia.
Keywords: revetment; moment stability analysis; factor of safety; embankment stability; articulated concrete blocks; Concrete blocks -- Stability; Slopes (Soil mechanics) -- Stability; Embankments -- Design and construction -- Testing; Retaining walls -- Design and construction -- Testing